Impact of Unemployment on Indian Society and Economy: General Analysis: भारतीय समाज एवं अर्थव्यवस्था पर बेरोजगारी का प्रभाव: सामान्य विश्लेषण - Bohra, Alka; Bohra, Jai Babber (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Unemployment or disconnection is a serious social and economic problem with far-reaching consequences everywhere, but it is sometimes overlooked. To better understand the causes of unemployment and ways to solve them, a more robust way of assessing unemployment must be applied. Our tendency to think about unemployment in terms of numbers only increases the sense of continuity that is associated with the history of unemployment. Crime statistics, poverty statistics, health statistics and, increasingly, market statistics all play a role in the social and economic life of countries. However, few of these statistics deal with the impact or cultural significance of unemployment rates. Abstract in Hindi Language: बेरोजगारी या विच्छेद एक गंभीर सामाजिक और आर्थिक समस्या है। जिसके दूरगामी परिणाम हर जगह हैं, लेकिन कभी-कभी इसे अनदेखा कर दिया जाता है। बेरोजगारी के कारणों और उन्हें हल करने के तरीकों को बेहतर ढंग से समझने के लिए, बेरोजगारी का आकलन करने का एक अधिक मजबूत तरीका लागू किया जाना चाहिए। बेरोजगारी के बारे में संख्याओं के संदर्भ में सोचने की हमारी प्रवृत्ति केवल उस निरंतरता की भावना को बढ़ाती है जो बेरोजगारी के इतिहास से जुड़ी हुई है। अपराध के आँकड़े, गरीबी के आँकड़े, स्वास्थ्य के आँकड़े और, तेजी से बढ़ते हुए, बाजार के आँकड़े सभी देशों के सामाजिक और आर्थिक जीवन में भूमिका निभाते हैं। हालाँकि, इनमें से कुछ आँकड़े बेरोजगारी दर के प्रभाव या सांस्कृतिक महत्व से सरोकार नहीं रखते हैं। Keywords: भारत, बेरोजगारी या विच्छेद, सामाजिक प्रभाव, आर्थिक प्रभाव।